Association of a FAM13A variant with interstitial lung disease in Japanese rheumatoid arthritis - Hiroshi Furukawa; Kota Shimada; Toshihiro Matsui; Shigeto Tohma; Masao Katayama; Shouhei Nagaoka; Shinichiro Tsunoda; Satoshi Shinohara; Kiyoshi Migita; Koichiro Saisho; Shomi Oka; Satoshi Ito; et al. (RMD Open, 2023)
Background Interstitial lung disease (ILD) occasionally occurs in rheumatoid arthritis (RA) and confers a dismal prognosis. We previously reported that a single-nucleotide variant (SNV) of MUC5B was associated with ILD in RA. However, the pathogenesis of ILD in Japanese patients with RA could not be explained solely by this SNV because its frequency is extremely low in the Japanese population. Here, we examined whether a different idiopathic pulmonary fibrosis susceptibility SNV might be associated with ILD in Japanese patients with RA.Methods Genotyping of rs2609255 (G/T) in FAM13A was conducted in 208 patients with RA with ILD and 420 without chronic lung disease using TaqMan assays.Results A significant association with usual interstitial pneumonia (UIP) in RA was detected for rs2609255 under the allele model (p=0.0092, Pc=0.0276, OR 1.53, 95% CI 1.12 to 2.11) and recessive model for the G allele (p=0.0003, Pc=0.0009, OR 2.63, 95% CI 1.59 to 4.32). FAM13A rs2609255 was significantly associated with UIP in male patients with RA (p=0.0043, OR 3.65, 95% CI 1.52 to 8.73) under the recessive model.Conclusions This study is the first to document an association of rs2609255 with ILD in Japanese patients with RA, implicating it in the pathogenesis of UIP, though studies on the function of rs2609255 are warranted.